The effect of depth on the morphology, bacterial clearance, and respiration of the mediterranean sponge chondrosia reniformis (Nardo, 1847) - Gokalp, M. (2020)
To support the successful application of sponges for water purification and collagen production, we evaluated the effect of depth on sponge morphology, growth, physiology, and functioning. Specimens of Eastern Mediterranean populations of the spongeÂ Chondrosia reniformisÂ (Nardo, 1847) (Demospongiae, Chondrosiida, Chondrosiidae) were reciprocally transplanted between 5 and 20 m depth within the KaÅ -Kekova Marine Reserve Area. Control sponges at 5 m had fewer but larger oscula than their conspecifics at 20 m, and a significant inverse relationship between the osculum density and size was found inÂ C. reniformisÂ specimens growing along a natural depth gradient. Sponges transplanted from 20 to 5 m altered their morphology to match the 5 m control sponges, producing fewer but larger oscula, whereas explants transplanted from 5 to 20 m did not show a reciprocal morphological plasticity. Despite the changes in morphology, the clearance, respiration, and growth rates were comparable among all the experimental groups. This indicates that depth-induced morphological changes do not affect the overall performance of the sponges. Hence, the potential for the growth and bioremediation ofÂ C. reniformisÂ in mariculture is not likely to change with varying culture depth. The collagen content, however, was higher in shallow waterÂ C. reniformisÂ compared to deeper-growing sponges, which requires further study to optimize collagen production.